2019
DOI: 10.1016/j.heliyon.2019.e02498
|View full text |Cite
|
Sign up to set email alerts
|

Electroconductive PEDOT:PSS-based hydrogel prepared by freezing-thawing method

Abstract: Biopolymer-based composition with adding of conductive polymer poly-(3,4-ethylenedioxythiophene) polystyrenesulfonate (PEDOT PSS) was made by mixing of iota-carrageenan (CRG), polyvinyl alcohol (PVA) and PEDOT PSS followed by freezing/thawing cycles. The method is environmentally friendly and based on the formation of polymer matrix upon of mixing CRG, PVA and PEDOT PSS and formation of porous physical gel due to freezing/thawing cycles. It is necessary to mention that all components are well-known as biocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The tensile strength (30-70 kPa) and elongation at break (114%-239%) also displayed an elevation in mechanical properties. 60,61 Hence, it is quite difficult to speculate on the behavior of hydrogels based on the concentration of PEDOT:PSS, as it can act in both ways, i.e. it can lead to either improvement or deterioration of the mechanical properties of the hydrogel, which is in accordance with our observations.…”
Section: Wileyonlinelibrarycom/journal/pisupporting
confidence: 87%
See 1 more Smart Citation
“…The tensile strength (30-70 kPa) and elongation at break (114%-239%) also displayed an elevation in mechanical properties. 60,61 Hence, it is quite difficult to speculate on the behavior of hydrogels based on the concentration of PEDOT:PSS, as it can act in both ways, i.e. it can lead to either improvement or deterioration of the mechanical properties of the hydrogel, which is in accordance with our observations.…”
Section: Wileyonlinelibrarycom/journal/pisupporting
confidence: 87%
“…Recent reports on different polymeric hydrogels with varying PEDOT:PSS concentrations support our observation. [60][61][62] Figure 9 shows a clear trend in the conductivity with respect to the PEDOT:PSS concentration. It also displays that even the hydrogel without PEDOT:PSS has a not negligible conductivity.…”
Section: Conductivitymentioning
confidence: 99%
“…PPy, another widely studied CP, is the oxidative polymerisation of pyrrole with a formula of H(C 4 H 2 NH) n H. As with other CPs, PPy is commonly blended with other biodegradable polymers in tissue engineering. Liang et al (2021) successfully fabricated conductive PPy-encapsulated silk fibroin (SF) fibres through electrospinning for cardiac tissue engineering, and the team revealed that the ratio of PPy to SF at 15:85 provided sufficient electrical conductivity for cardiomyocytes [131]. By using fibroblasts and OLN-93 neural cells, nanochitosan-PPy film of a 2:10 ratio was shown to be biocompatible and non-cytotoxic with an electrical conductivity of 1 × 10 −3 S cm −1 , which is valuable in neural tissue engineering [121].…”
Section: Conducting Polymers (Cps)mentioning
confidence: 99%
“…51,52 On the other hand, in electron-conducting hydrogels (or just conductive hydrogels) the mobilization of electrons occurs through π-electron conjugation along the polymer chains. 44 For this matter, conductive polymers (CPs), such as polyaniline, polypyrrole, 53 or poly(3,-4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT:PSS), 54,55 are used as the main component in hydrogel production. Also, the addition of conductive components, such as metallic nanoparticles/nanowires 56 or carbon-based nanomaterials, 57,58 within the polymer matrix may improve the conductivity of the hydrogel.…”
Section: Structure and Conductivity Of Hydrogelsmentioning
confidence: 99%